Kepemimpinan Berbasis Core Values Sekolah Unggulan di Malang - Muh. Hambali (MANAGERIA: Jurnal Manajemen Pendidikan Islam, 2017)
AbstractVortex of globalization necessitates a school establishes certain advantages and challenges of the proliferation of educational institutions, if private schools are not improving the human resource and does not indicate a particular advantage innovations from other schools will be degraded public trust. A school principal requires a model of leadership in creating a level of trust and quality of academic services that exceed the expectations of internal and external school school. School leadership puts the organization a competitive advantage as a core value as the value inherent in a school community. The competitive advantage of the organization is how the organization creates value service performance advantages of low cost and product differentiation. Two such approaches are needed schools that want to deliver maximum quality academic services and demonstrate excellence by means of efficiency. The goal is to assess school leadership based on core values, characteristics of quality implementation in schools and the implementation of the concept of quality assurance systems. Three objectives are based on research and discussion of literature that leadership with the guarantee is related to the value system that was built through the vision that inspired each school community. The vision of leadership based on values ​​that are mutually agreed upon has spawned a school of excellence amidst the proliferation of educational institutions. Educational institutions are not seen as a social investment, but the institution has become a noble industry. Based on the explanation, the leadership of principals need to have different perspectives on quality assurance paradigm is very different between the service field service with the service areas of goods. Notch education that are in the area of ​​services.Keywords: core values-based leadership, excellent schools